Flame-made niobium doped zinc oxide nanoparticles in bulk heterojunction solar cells - Kruefu V. (2017)
We report fabrication and measurement of bulk heterojunction solar cells utilizing a poly(3-hexylthiophene) (P3HT), phenyl- C61 -butyric acid methyl ester (PCBM) composite loaded with different concentrations of niobium doped zinc oxide (Nb/ZnO) nanoparticles produced by flame spray pyrolysis. Nanoparticles with different niobium concentrations were compared, along with devices without Nb/ZnO nanoparticles and with undoped ZnO nanoparticles. It was found that niobium doping leads to a slight increase in open circuit voltage and an increase in short circuit current that scales with niobium concentration. Additional comparison was made between the nanoparticles with 3% niobium by weight to unloaded devices. These also showed a similar open circuit voltage increase and an increase in current that scales with Nb/ZnO nanoparticle concentration to 30% by volume and drops off at 33% Nb/ZnO by volume. Possible mechanisms for these improvements are discussed. © 2010 American Institute of Physics.